Aberrant reward prediction errors in young adult at‐risk alcohol users. (23rd January 2020) - Cao, Zhipeng; Bennett, Marc; O'Halloran, Laura; Pragulbickaite, Gabija; Flanagan, Luke; McHugh, Louise; Whelan, Robert
Abstract: Previous studies suggest that individuals with substance use disorder have abnormally large responses to unexpected outcomes (reward prediction errors [RPEs]). However, there is much less information on RPE in individuals at risk of alcohol misuse, prior to neurobiological adaptations that might result from sustained alcohol use. Here, participants (mean age 23.77 years, range 18‐32 years) performed the electrophysiological monetary incentive delay task. This task involved responding to a target stimulus following reward incentive cues to win, or avoid losing, the cued reward while brain activity was recorded under 64‐channel EEG. The Alcohol Use Disorders Identification Test (AUDIT) was used to quantify at‐risk alcohol use, with high (n = 22, mean AUDIT score: 13.82) and low (n = 22, mean AUDIT score: 5.77) alcohol use groups. Trial‐by‐trial RPEs were estimated using a Rescorla‐Wagner reinforcement model based on behavioral data. A single‐trial analysis revealed that the feedback‐related negativity (FRN) and feedback P3 (fb‐P3) event‐related potential components were significantly modulated by RPEs. There was increased RPE‐related fb‐P3 amplitude for those in the high alcohol use group. Next, the mean amplitude of ERPs elicited by positive and negative RPEs were compared between groups. We found that high alcohol use participants had attenuated FRN amplitude in contrast with low alcohol use participants for both positive and negative RPEs but enhanced fb‐P3 for both positive and negative RPE. These results, with differences in RPE in an at‐risk group, suggest that RPE a potential vulnerability marker for alcohol use disorder. Abstract : The Alcohol Use Disorders Identification Test (AUDIT) was used to quantify at‐risk alcohol use, with high and low alcohol use groups (mean AUDIT scores of 13.82 and 5.77, respectively). Trial‐by‐trial reward prediction errors were estimated using a Rescorla‐Wagner reinforcement model based on behavioral data under 64‐channel EEG. We found that high alcohol use participants had attenuated feedback‐related negativity amplitude in contrast with low alcohol use participants for both positive and negative RPEs but enhanced feedback P3 for both positive and negative RPE.